Acute Effects of Different Alcohol Doses on Psychomotor Performance and Subjective Responses among Healthy Young Women in China - Xiaoqin Yi; Li Xiao; Jin Xiang; Weihao Fan; Yingqiang Fu; Linchuan Liao; Yi Ye (Journal of Forensic Science and Medicine)
Introduction: Alcohol abuse often precipitates traffic accidents or other mishaps due to its impact on psychomotor ability and subjective emotions. The multifaceted nature of impairment is chiefly influenced by dosage, yet there remains a dearth of research concerning the effects of alcohol consumption on driving ability among female Chinese individuals across varying doses. This study aims to investigate the influence of three different alcohol doses on changes in alcohol metabolism, psychomotor performance, and subjective response in Chinese females. Materials and Methods: Three dosage levels (0.2 g/kg, 0.6 g/kg, and 1.0 g/kg) were administered to 11 subjects with the genotype ADH1B*1/*2-ADH1C*1/*1-ALDH2*1/*1 in an acute drinking challenge. Blood pressure and heart rate were monitored using an electronic wrist blood pressure monitor at specific intervals, while blood alcohol concentration (BAC) and blood acetaldehyde concentration (BAAC) were analyzed via headspace gas chromatography. Psychomotor function was evaluated using auditory simple reaction time (ASRT), visual choice reaction time (VCRT), pursuit rotor task (PRT), and digit symbol substitution test (DSST). The Biphasic Alcohol Effects Scale (BAES) was employed to measure excitement and inhibition emotions. Data analysis utilized repeated-measures analyses of variance. Results: Across the three dosage levels, no significant differences in blood pressure and heart rate were observed compared to predrinking levels. Notably, at doses of 0.6 g/kg and 1.0 g/kg, BAC and BAAC exhibited significant increases compared to baseline levels at various postdrinking time points. Reaction times for ASRT and VCRT were notably prolonged at 1 and 2 h postdrinking with a dose of 1.0 g/kg, while DSST showed increased reaction time and decreased accuracy at 1 h postdrinking. Conversely, no significant differences were detected in other tests or at lower doses (0.2 g/kg and 0.6 g/kg). Moreover, BAES scores for excitement and inhibition remained consistent across different alcohol doses compared to predrinking levels. In addition, the findings suggest a correlation between psychomotor impairment and BAC. Conclusion: The findings of this study align with previous trends, indicating that higher alcohol doses exacerbate impairments in psychomotor functions, leading to heightened risks of traffic accidents or other incidents.